P184 Age should not be a barrier to pulmonary endarterectomy in carefully selected patients. (15th November 2017) - Newnham, M; Hernandez-Sanchez, J; Dunning, J; Ng, C; Tsui, S; Bunclark, K; Sheares, K; Taboada, D; Toshner, M; Pepke-Zaba, J; Jenkins, D; Cannon, J
Abstract : Introduction: We previously reported that hospital survival in patients over 70 years undergoing pulmonary endarterectomy (PEA) was comparable to those under 70, albeit with longer hospital and intensive care unit (ICU) stays. 1 Octogenarians have acceptable morbidity and mortality outcomes following cardiac surgery. We aimed to assess if this also applies to PEA surgery. Methods: Consecutive patients undergoing PEA for chronic thromboembolic pulmonary hypertension (CTEPH) from June 2006 to August 2016 at the National referral centre for PEA were included in a retrospective analysis. The cohort was dichotomized into over and under 80 years according to age at surgery. Pre-operative baseline and post-operative 3–6 month follow-up data were recorded, with follow-up data included until November 2016. Results: 1152 individuals underwent PEA (1115 under 80 years, 37 over 80) during the study period. Baseline and 3–6 month follow up variables and outcomes are summarised in Table 1 . Survival is lower in the over 80 group (Log-rank test, p=0.002), but is no different from an age and sex matched UK reference population (p=0.5) (Office of National Statistics). The hospital length of stay was longer in those over 80 (median: 19 vs. 14 days; p=0.001), however, there was no difference in NYHA class, haemodynamics, type of surgical disease, CAMPHOR score or ICU length of stay between the two age groups. There were more concomitant cardiac surgical procedures in the over 80 group (26% vs 11%, p=0.006), although this was not statistically significant when accounting for multiple testing. Conclusions: We found similar outcomes in patients under and over 80 years old undergoing PEA, except for a prolonged hospital length of stay in those over 80. Whilst survival is reduced in the over 80 group compared to the under 80, it is no different to the age-sex matched population. Age alone should not be a contraindication for PEA and individuals with suspected CTEPH should be referred for specialist evaluation. Reference: Berman M, Hardman G, Sharples L, Pepke-Zaba J, Sheares K, Tsui S, et al. Pulmonary endarterectomy: Outcomes in patients aged ≥70. Eur J Cardiothorac Surg2012;41(6):154–60.